2020
DOI: 10.1177/1440783320919173
|View full text |Cite
|
Sign up to set email alerts
|

Youth, social cohesion and digital life: From risk and resilience to a global digital citizenship approach

Abstract: Cultural diversity and the digital have been identified as among the most important megatrends facing young Australians in current times. These challenges have been addressed primarily through a siloed risk/protection approach, with research and policy/programme formulation focusing on either social cohesion in the ‘offline’ world, particularly risks/protective factors for those identified as culturally and linguistically diverse (CALD) youth; or digital risks/protective factors regarding cyber-safety for main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Although this paper is primarily interested in developing an Australian-based race critical youth studies, it is important to acknowledge that young people in Australia are also living global lives (Robertson, Harris, and Baldassar 2018) most commonly via social media and increased transnational connectivity (Harris and Johns 2020) wherein their consumption choices and everyday lives are shaped by popular cultures and political issues abroad. For example, they are, therefore, knowledgeable about and deeply affected by institutional racism abroad that might have negative effects on their family or community, for example the Muslim travel ban in the U.S in effect in 2018, police brutality against African American young people that mirrors the experiences of Indigenous Australian populations.…”
Section: Class Without Race and Multiculture Without Class?mentioning
confidence: 99%
“…Although this paper is primarily interested in developing an Australian-based race critical youth studies, it is important to acknowledge that young people in Australia are also living global lives (Robertson, Harris, and Baldassar 2018) most commonly via social media and increased transnational connectivity (Harris and Johns 2020) wherein their consumption choices and everyday lives are shaped by popular cultures and political issues abroad. For example, they are, therefore, knowledgeable about and deeply affected by institutional racism abroad that might have negative effects on their family or community, for example the Muslim travel ban in the U.S in effect in 2018, police brutality against African American young people that mirrors the experiences of Indigenous Australian populations.…”
Section: Class Without Race and Multiculture Without Class?mentioning
confidence: 99%
“…Additionally, school settings are becoming increasingly more diverse because large numbers of students are from different ethnic, cultural, or religious backgrounds [13]. In this sense, authors like Harris and Johns [14] claim that this situation has been identified as one of the major trends causing youngsters to quarrel in their digital interactions. This leads to a type of cyberbullying caused by intolerance and lack of empathy towards students of different cultures and religions [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies have also drawn attention to issues of social cohesion, resilience and belonging for young people of migrant and refugee backgrounds, with both this group and Aboriginal and Torres Strait Islander young people in Australia reporting widespread incidences of discrimination online (Carlson and Frazer, 2018;Caluya et al 2018;Harris & Johns 2020). A study of the digital citizenship of culturally and linguistically diverse (CALD) youth conducted by the Centre for Multicultural Youth and University of Melbourne researchers found that those who were politically active online were more likely to experience harassment and bullying (Caluya et al 2018: 5).…”
Section: The Policy Issuementioning
confidence: 99%